Thermal properties, nanoscopic structure and swelling behavior of chitosan/(ureasil–polyethylene oxide hybrid) blends - Paredes Zaldivar, Mayté [UNESP]; Santilli, Celso Valentim [UNESP]; Peniche Covas, Carlos Andrés; Pulcinelli, Sandra Helena [UNESP] (Springer Nature, 2017)
In this work, the effect of chitosan blending on the thermal properties, nanoscopic structure and swelling behavior of ureasil–polyethylene oxide (U-PEO) hybrid materials was examined. Materials were prepared by the sol–gel route using acid catalysts, and the effect of acid (hydrochloric or acetic acid) was also examined. Differential scanning calorimetry results showed that chitosan addition did not provoke appreciable changes in the thermal behavior of the U-PEO. Thermogravimetric curves did not show changes in thermal stability resulting from chitosan blending but were depended on the type of acid catalyst. Small-angle X-ray scattering and nuclear magnetic resonance spectroscopy techniques were used for studying nanoscopic and inner structures, showing the existence of two structural levels and differences in polycondensation degrees. All samples presented fast water uptake with the same initial swelling rate and with a non-Fickian or anomalous transport mechanism. Swelling degree was higher in hybrids prepared with HCl, which possessed less branched siloxane cross-link nodes species, therefore lower polycondensation degree. Also, the magnitude of swelling decreased for hybrids blended with chitosan, which provides a means of tailoring the water uptake by the ureasil–PEO hybrid and to potentiate the control of the release profile of drugs incorporated in these materials.
Keywords: Chitosan; Hybrid materials; Nanoscopic structure; Swelling degree; Thermal properties